ANALISIS LIKUIDITAS, SOLVABILITAS DAN RENTABILITAS TERHADAP KINERJA PT JOYMAR EXPRESS PENAJAM PASER UTARA - ANITA KARINA (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2016)
Study that used in this research is descriptive method, which done research which measurement on numbers of  financial report which needed later for comparing liquidity ratio result, solvency, and profitability  from years apart to found out the development. After had measure the financial report of PT Joymar Express Penajam Paser Utara and had compared the numbers of each analytic instruments from earlier years, known that the liquidity ratio had decrease and for solvency and profitability result had increase from 2012 until 2014.Keyword: Liquidity, Solvency, Profitability